Controle de sistemas não-Markovianos - Souza, Francys Andrews de (2017)
In this thesis, we present a concrete methodology to calculate the epsilon-optimal controls for non-Markovian stochastic systems. A pathwise analysis and the use of the discretization structure proposed by Leão and Ohash jointly with measurable selection arguments, allows us a structure to transform an infinite dimensional problem into a finite dimensional. In this way, we guarantee a concrete description for a rather general class of stochastic problems.